THE ROLE OF CUSTOMER SATISFACTION IN MEDIATING THE INFLUENCE OF PRODUCT QUALITY ON REPURCHASE INTENTION (STUDY ON MIXUE PRODUCT CUSTOMERS IN DENPASAR CITY) - Sidney Muliarta; I Gede Ketut Warmika (Adisam Publisher, 2025)
The culinary business in Indonesia continues to develop every year. One thing that is currently popular among Indonesian people is tea and ice cream. These two dishes are very popular with various groups, from children to adults. This potential creates extensive business opportunities in the culinary sector. This research was conducted at the Mixue outlet in Denpasar City. The purpose of this research was to explain the role of customer satisfaction in mediating the influence of product quality on repurchase intentions among Mixue product customers. The sample in this study was 120 respondents. Data collection was carried out by distributing questionnaires via Google Form to make it easier for respondents to provide answers and be more practical. The collected data was analyzed using path analysis techniques, Sobel test, and VAF test. The results of this research show that product quality has a positive and significant effect on customer satisfaction; product quality has a positive and significant effect on repurchase intentions; customer satisfaction has a positive and significant effect on repurchase intention; and customer satisfaction is able to partially mediate the influence of product quality on repurchase intentions among Mixue product customers. The implications of this research can be material for consideration and input for Mixue in maintaining repurchase intentions by considering product quality and customer satisfaction.